The Role of Sport Innovation in Global Economics -The Hungarian Case - Korsos, Gyorgy; Szakonyi, Petra (9th FEB International Scientific Conference: Sustainable Management in the Age of ESG and AI: Navigating Challenges and Opportunities, 2025)
This paper examines the critical relationship between sports innovation and global economics, focusing specifically on the Hungarian context. As the sports industry continues to emerge as one of the fastest-growing sectors worldwide, it not only serves as a source of entertainment but also plays a significant role in economic activity, job creation, and community development. The study highlights the strategies employed by Hungarian football clubs to enhance organizational performance through technological advancements, knowledge management, and sustainable practices. By conducting a systematic literature review and analyzing empirical data from in-person interviews with representatives from several Hungarian football clubs, this research elucidates how innovation can drive economic growth by attracting investments, enhancing productivity, and fostering vibrant communities. The literature review emphasizes the importance of managerial knowledge, organizational culture, and external collaborations in achieving innovation success. Furthermore, it underlines the potential of sports innovation as a catalyst for economic growth, particularly through increased sports consumption, infrastructural investments, and community engagement. Ultimately, the findings of this study aim to provide valuable insights for practitioners and policymakers in the sports sector, demonstrating that embracing innovation can enhance competitive advantage and contribute meaningfully to both local and global economic landscapes.